2008
DOI: 10.1523/jneurosci.5295-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Bidirectional Communication between Cortex and Basal Ganglia during Movement in Patients with Parkinson Disease

Abstract: Cortico-basal ganglia networks are considered to comprise several parallel and mostly segregated loops, where segregation is achieved in space through topographic connectivity. Recently, it has been suggested that functional segregation may also be achieved in the frequency domain, by selective coupling of related activities at different frequencies. So far, however, any coupling across frequency in the human has only been modeled in terms of unidirectional influences, a misplaced assumption given the looped a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
174
3
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(207 citation statements)
references
References 44 publications
21
174
3
3
Order By: Relevance
“…The frontocentral topography of the beta-gamma component observed in the present study for positive feedbacks is compatible with the ventromedial prefrontal activations reported in studies on reward and punishment processing (Kim, Shimojo, & O'Doherty, 2006;Knutson, Fong, Bennett, Adams, & Hommer, 2003;Nieuwenhuis, Slagter, von Geusau, Heslenfeld, & Holroyd, 2005;Tom, Fox, Trepel, & Poldrack, 2007). A follow-up study has also suggested the possible dopaminergic origin of the beta-gamma activity (Marco-Pallarès et al, 2009), in convergence with recent studies showing that changes in dopamine levels are associated with the reestablishment of gamma band oscillations and a change from low-to high-oscillatory activity (Brown et al, 2001;Lalo et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…The frontocentral topography of the beta-gamma component observed in the present study for positive feedbacks is compatible with the ventromedial prefrontal activations reported in studies on reward and punishment processing (Kim, Shimojo, & O'Doherty, 2006;Knutson, Fong, Bennett, Adams, & Hommer, 2003;Nieuwenhuis, Slagter, von Geusau, Heslenfeld, & Holroyd, 2005;Tom, Fox, Trepel, & Poldrack, 2007). A follow-up study has also suggested the possible dopaminergic origin of the beta-gamma activity (Marco-Pallarès et al, 2009), in convergence with recent studies showing that changes in dopamine levels are associated with the reestablishment of gamma band oscillations and a change from low-to high-oscillatory activity (Brown et al, 2001;Lalo et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Last, given the dense connections between the CMA and the BG [particularly the anterior putamen (McFarland and Haber, 2000;Takada et al, 2001)] and given the detrimental effect of dopamine depletion on corticostriatal connectivity (Lalo et al, 2008), we directly tested whether effective connectivity between these structures would change as a function of disease severity. Switch-related effective connectivity between the CMA and the most affected BG significantly decreased as a function of lateralized disease severity (left GP, r ϭ Ϫ0.71, p ϭ 0.039 corrected, local maximum at [Ϫ20 4 2]; left putamen, r ϭ Ϫ0.80, p ϭ 0.007 Figure 3.…”
Section: Relationship Between Cerebral Effects and Disease Severitymentioning
confidence: 99%
“…Coherent gamma frequencies occur between the thalamus and cortex (Pedroarena and Llinas 2001), cortex and cerebellum (Soteropoulos and Baker 2006), cerebellum and thalamus (Timofeev and Steriade 1997), and hippocampus and cortex (Buzsáki 2006). Gamma activity in the motor cortex lags behind coherent activity in subcortical structures (Lalo et al 2008;Litvak et al 2012), suggesting that gamma synchronization reflects an arousal-related event for enabling initiation of movement (Brucke et al 2012;Cheyne and Ferrari 2013;Jenkinson et al 2013). In addition, we showed that every cell in the reticular activating system (RAS), especially the pedunculopontine nucleus (PPN), plateaus at gamma frequencies (Kezunovic et al 2011;Simon et al 2010;Urbano et al 2012).…”
mentioning
confidence: 99%